A Challenge to Divine Psychologism. Issue 2 (2nd April 2016) - Fried, Greg
ABSTRACT: Alvin Plantinga proposes that mathematical objects and propositions are divine thoughts. This position, which I call divine psychologism, resonates with some remarks by contemporary thinkers. Plantinga claims several advantages for his position, and I add another: it helps to explain the glory of mathematics. But my main purpose is to issue a challenge to divine psychologism. I argue that it has an implausible consequence: it identifies an entity with God's relation to that entity. I consider and rebut several ways in which a divine psychologist might argue that this is not really a consequence, or that the identification is plausible.